2017
DOI: 10.1038/s41598-017-12013-2
|View full text |Cite
|
Sign up to set email alerts
|

Preserved immune functionality and high CMV-specific T-cell responses in HIV-infected individuals with poor CD4+ T-cell immune recovery

Abstract: Poor CD4+ T-cell recovery after cART has been associated with skewed T-cell maturation, inflammation and immunosenescence; however, T-cell functionality in those individuals has not been fully characterized. In the present study, we assessed T-cell function by assessing cytokine production after polyclonal, CMV and HIV stimulations of T-cells from ART-suppressed HIV-infected individuals with CD4+ T-cell counts >350 cells/μL (immunoconcordants) or <350 cells/μL (immunodiscordants). A group of HIV-uninfected ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
(66 reference statements)
1
8
0
Order By: Relevance
“…Few previous studies evaluated CMV-specific polyfunctionality in PLWHIV, but recently, maintained polyfunctionality was found in CMV-specific terminally differentiated T-cells from ART-naïve PLWHIV 60 , and in CMV-specific memory CD4+ T-cells from long-term nonprogressors despite inflation of these cells 61 . In accordance with our results, a very recent study showed maintained CMV-specific T-cell polyfunctionality despite phenotypic T-cell alterations in PLWHIV treated with cART 62 . The importance of maintained polyfunctionality is still debated, and an important consideration is, that polyfunctionality may not necessarily be beneficial in PLWHIV, if accompanied by increased immune pathology or tissue damage through high release of cytokines.…”
Section: Discussionsupporting
confidence: 93%
“…Few previous studies evaluated CMV-specific polyfunctionality in PLWHIV, but recently, maintained polyfunctionality was found in CMV-specific terminally differentiated T-cells from ART-naïve PLWHIV 60 , and in CMV-specific memory CD4+ T-cells from long-term nonprogressors despite inflation of these cells 61 . In accordance with our results, a very recent study showed maintained CMV-specific T-cell polyfunctionality despite phenotypic T-cell alterations in PLWHIV treated with cART 62 . The importance of maintained polyfunctionality is still debated, and an important consideration is, that polyfunctionality may not necessarily be beneficial in PLWHIV, if accompanied by increased immune pathology or tissue damage through high release of cytokines.…”
Section: Discussionsupporting
confidence: 93%
“…We suspect that since there is a massive production of IgG antibodies during a secondary immune response to a pathogen, there could be reactivation of CMV resulting in the surge of anti-CMV IgG production (27). However, due to compromised immunity especially in the HIV-infected individuals and immune senescence associated with HIV and CMV itself, there may be failure to mount an IgM immune response, sufficient to be detected by the ELISA (15). This results in underestimation of active CMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Total CD4 + T-cell count > 400 cells/µl at 2 years after ART initiation, with plasma HIV RNA < 50 copies/ml. 48,105,106,241 Total CD4 + T-cell count < 350 cells/µl and/or increase in the CD4 + T-cell count < 30% from baseline at 1-10 years after ART initiation, with an undetectable plasma VL.…”
Section: Definition Of "Immunological Nonresponder" Definition Of "Immentioning
confidence: 99%